Okja [videorecording (DVD)] - Swinton, Tilda; Dano, Paul, 1984-; An, Seo-hyun; Byun, Hee-bong; Yeun, Steven; Collins, Lily, 1989-; Yun, Che-mun, 1970-; Henderson, Shirley, 1965-; Henshall, Daniel, 1983-; Bostick, Devon, 1991-; Ch'oe, U-sik, 1990-; Esposito, Giancarlo; et al. (Criterion collection, 2022)
Mija is a South Korean girl growing up on an Edenic mountainside with her grandfather and best friend: Okja, a giant, empathetic "super pig" created as part of a secret GMO experiment. When Okja is abruptly torn away from her, Mija embarks on a perilous rescue mission that places her at the center of a sinister corporate conspiracy. While Bong's trademark virtuosic set-pieces dazzle, Okja's beating heart is the connection between a girl and her super pig, made all the more poignant by the brilliant special effects that bring the animal star to unforgettable life.